METHODOLOGY OF ESTIMATING OF LIMNOLOGICAL CHARACTERISTICS SPATIAL DISTRIBUTIONS ABNORMALITY ON THE EXAMPLE OF LAKE LADOGA SURFACE WATER TEMPERATURE FIELDS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Use of probabilistic approach for estimating of synoptic-scale abnormality is shown. Anomalous deviations of real in situ Lake Ladoga surface temperatures from typical ones were estimated with the data obtained during 43 expeditions 1960 – 2003. These deviations were mapped and statistically analyzed. A degree of spatiotemporal abnormality of real temperature fields, its features and heterogeneous character were revealed. The scales of thermal inhomogeneity are obtained from computation of two-dimensional spatial autocorrelation functions within the random function network. Ways of analysis of characteristics of anomalies fields’ correlation ellipses are given. Applicability of the methodology and the results is suggested.